Reliquary ebook - Preston, Douglas (Pendergast, 2010)
Reliquary is the smash hit second book in the Pendergast series, from New York Times bestselling authors Douglas Preston and Lincoln Child Hidden deep beneath Manhattan lies a warren of tunnels, sewers, and galleries, mostly forgotten by those who walk the streets above. There lies the ultimate secret of the Museum Beast. When two grotesquely deformed skeletons are found deep in the mud off the Manhattan shoreline, museum curator Margo Green is called in to aid the investigation. Margo must once again team up with police lieutenant D'Agosta and FBI agent Pendergast, as well as the brilliant Dr. Frock, to try and solve the puzzle. The trail soon leads deep underground, where they will face the awakening of a slumbering nightmare... in Reliquary , from bestselling coauthors Douglas Preston and Lincoln Child. At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.